Implementasi Kebijakan Kepala Badan Pertanahan dalam Proses Pemisahan Sertifikat Tanah - Desi Fitriyana; Syarifuddin, Haeruddin; D, Herman (Yayasan Literasi Sains Indonesia, 2025)
Land plays a strategic role in people's lives because it forms the basis of social, economic, and legal activities. Legal certainty regarding land ownership is realized through the issuance of certificates, including through the mechanism of land certificate separation. This study aims to determine how the Head of the Land Agency implements policies in the process of land certificate separation and to identify the factors that influence it. The research was conducted at the Sidenreng Rappang District Land Office using a descriptive qualitative method. Data were obtained through interviews, observations, and documentation, then analyzed using NVivo 12 software to map themes, patterns, and relationships between data. The results of the study show that the land certificate separation policy provides tangible benefits to the community, particularly in terms of legal certainty, ease of economic transactions, and family asset management. However, the implementation of the policy still faces obstacles in the form of limited human resources, technical barriers in the use of applications, and a lack of public understanding of procedures and land boundaries. Institutional factors, compliance of implementers, and responsiveness to community needs also greatly influence the success of the policy. This study emphasizes the importance of increasing the capacity of the apparatus, optimizing information technology, and increasing socialization to the community in order to realize transparent, efficient, and accountable land certificate separation services.